Study Of Crack Propagation On Component (Multilayer Ceramic Capacitor) During Reflow Soldering Process - Azman, Muhammad Aliff Zikri (Universiti Sains Malaysia, 2021)
Multilayer Ceramic Capacitor (MLCC) is a Surface Mounted Device (SMD) type capacitor that is currently used in wide ranges of capacitance functions. Because of its improved frequency characteristics, higher reliability, and higher withstanding voltage, MLCC receives more attention than other capacitors these days. For applications requiring tiny capacitances, MLCC are typically the capacitor of choice. They are employed as bypass capacitors, as well as in op-amp circuits, filters, and other applications. However, during surface mounted technology (SMT) process, for example, reflow soldering process, this capacitor might have defected and fracture due to the thermal shock and undetermined pressure inside the capacitor that comes from many factors. Two types of MLCC are compared from the simulation and studied. The reflow soldering process is simulated and applied to the geometry to be simulated. A few techniques on how to conduct the research has been discussed and one has been chosen. Effects of vapor pressure and the build-up pressure inside the capacitor is reviewed. Also, the effect of different solder materials has been analysed and studied throughout this project.